Amendments to the Audit Report for the Review of International Standards on Auditing - Mortură Laura-Alexandra (Ovidius University Annals: Economic Sciences Series, 2017)
As a result of the last economic and financial crisis, the auditors' impact on its triggering wasquestioned, as the opinion expressed by the auditors directly influenced, the decisions taken by theusers of the financial and accounting information, namely the investors. The sign of question on theauditors 'work was also due to a lack of knowledge of the auditors' responsibility by the users. Theopinion issued by the auditor provides reasonable, but not absolute, assurance on the informationprovided by the financial statements, in which case the auditor's responsibility is limited. Tomitigate these discrepancies, the International Auditing and Assurance Standards Board (IAASB)has developed projects that have generated solutions to improve International Standards onAuditing. Thus, in 2015, the IAASB issued a new edition of the International Auditing Standards,which made changes in the drafting of the audit report.